DISPARITAS WILAYAH ANTAR KECAMATAN DI KABUPATEN SLEMAN - Yeremias T Keban; Ihsan Yoga Triyanto (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
The process of economic development in Sleman Regency to result in economic growth that is marked by an increase in GDP per capita in this regency. However, the rate of economic growth and GDP per capita in each sub-regency has a different value, thus causing disparity between regions. The purposes of this study are: (1) to describe the regional disparity problem among sub-regency in Sleman Regency in period of 2008-2016, (2) to determine the factors influencing that regional disparity level. To achieve the purposes, the data used are secondary data of 2008-2016 obtained from the BPS (The Central Bureau of Statistics), and the methods used are Williamson Index, panel data regression, and descriptive analysis. The findings of the study are (1) the regional disparity among sub-regency in Sleman Regency tends to decrease during the observation period from 2008 to 2016. Williamson Index showed the moderate level of disparity with mean of index value is 0.3986, (2) the most influential factors on the regional disparity are number of health facilities and tertiary sector contribution. The results of this study hopefully will provide useful information for the local government of Sleman Regency to design regional or sectoral development policy and is expected to contribute to further research on issues of regional development.